A Self‐Assembled Rectangular Host with Terpyridine–Platinum(II) Moieties That Binds Unsubstituted Pentacene in Solution (Eur. J. Org. Chem. 9/2016). Issue 9 (March 2016) - Yamaki, Yusuke; Nakamura, Takashi; Suzuki, Sayuri; Yamamura, Masaki; Minoura, Mao; Nabeshima, Tatsuya
Abstract : The cover picture shows a supramolecular host that encapsulates unsubstituted pentacene. Pentacene has attracted much attention as an organic electric material, but it often suffers from its very low solubility. The self‐assembled rectangular host shown in the picture has two pairs of terpyridine–platinum(II) moieties aligned parallel to each other and connected by diyne linkers. The host encapsulates the unsubstituted pentacene with a remarkably strong binding constant, and solubilizes it in acetonitrile up to the millimolar level. For the smaller acenes (naphthalene to tetracene), a planar arrangement of two molecules inside the cavity is achieved. Details are discussed in the article by T. Nabeshima et al. on p.1678 ff .